Dimensions of Judges Independence in The Judicial Process - Jufri, Supriadi; Yasmin, Muhammad; Fitria, Ika; Cahyani, Afrilia; Adhilia, Lia Trizza Firgitta (Alauddin Law Development Journal, 2024)
This research aims to analyze and criticize the independence of judges in maintaining integrity and social trust in the judicial process. This type of research is normative research. The results showed that factors that can affect the independence of judges in carrying out their duties. Judges in resolving conflicts faced by them must be able to resolve objectively based on applicable law and the concept of judge independence is a fundamental principle in the judicial system which emphasizes that judges must be able to carry out their duties independently, without pressure or influence from any party. The independence of judges is an important prerequisite in maintaining integrity, fairness and trust in the judicial process in a country. The presence of independent judges ensures that the judicial process is transparent, fair, and in accordance with the principles of democracy and the rule of law.